SecA protein is required for translocation of a model precursor protein into inverted vesicles of Escherichia coli plasma membrane. - Watanabe, M (1993)
We have investigated whether the SecA protein is required for in vitro translocation of a model presecretory protein into inverted vesicles (INV) of the Escherichia coli plasma membrane. Contrary to previous reports, we found that urea-extracted INV that contained only the membrane-integral form of SecA were fully translocation active. Proteoliposomes that were reconstituted from a detergent extract of INV did contain a full complement of membrane-integral SecA but < 1% of SecY. These proteoliposomes were fully translocation active. However, immunodepletion of > 90% of the SecA from the detergent extract yielded proteoliposomes that were translocation inactive. Addition of purified SecA to the SecA-depleted proteoliposomes restored translocation. The amounts of SecA required to saturate translocation activity were equivalent to those present as membrane-integral SecA in INV. These data indicate that SecA is necessary for protein translocation, and reinforce our previous conclusion that SecY is not required. Contrary to previous reports, we find that membrane-integral SecA is not irreversibly inactivated by 6 M urea and that membrane-integral SecA and SecY do not form a stoichiometric protein complex in the membrane.